SCIENTIFIC AND METHODOLOGICAL BASES OF GPS MONITORING OF INTENSIVE MOVEMENTS OF THE EARTH’S CRUST IN THE EARTHQUAKE-PRONE REGIONS OF KAZAKHSTAN - Sh. Zhantayev, Zh.; Kaldybayev, A.A.; Nurakynov, S.M.; Urazaliyev, A.S.; Kairanbayeva, A.B. (Academic Scientific Journal of Computer Science, 2020)
Over the past 40 years, the damage caused by natural disasters in the world has increased 9 times, and their frequency 5 times, while the growth rate of economic damage from natural disasters exceeds the growth rate of industrial production. Disasters that have occurred in recent years are characterized by a large number of people who died at the same time. In this regard, the decisions of the United Nations, other international organizations and the law of the Republic of Kazakhstan emphasize that governments, international organizations and scientific institutions should be included in the fight against disasters, where Kazakhstan is no exception to the global patterns of emergencies and their negative impact on the social sphere and the environment. Over the past hundred years, destructive and catastrophic earthquakes have occurred in the seismically active territories of Kazakhstan, such as Vernensky (1887), Chilik (1889), Keminsky (1911), the latter, two of which are the strongest in the continental part of Eurasia for the whole history of observations. The occurrence of such seismic catastrophes in the future is very likely and is a consequence of the previous stages of the geological development of the region and its current geodynamic position. All this indicates the need to study the manifestations of geodynamic processes, identify precursors of seismic activity.